Development of Higher Order Thinking Skills (HOTS) Instruments on the Material of the Human Reproductive System - Lia Junita Harahap (Bioedunis Journal, 2023)
Biology require students to be able to think at a high level in understanding all concepts including material on the human reproductive system, must be able to unite or connect with other processes or systems that occur in the human body or connect with other biological concepts. This research and development aims to produce valid and reliable higher-order thinking skill instruments. So that it can be used as an alternative in measuring, training, and improving the ability to think at a high level in the human reproductive system. The method used in this research is (RD). This study’s instrument for high-level thinking skills in reproductive system material refers to the 4D development model (Define, Design, Develop, and Disseminate).